IDENTIFIKASI DAN ISOLASI DNA DAUN JERUK LEMON (Citrus limon (L.) Burm. f.) - Isazava, Khumairo Magfirotus; Frehadini, Natasya Irhene; Sandra, Ola Christiana; Puspita, Reflinda Sindy; Suci, Septiani Rahmat; Hosyana, Soraya Yedija; Aldana, Yohanes Andi; Cesa, Fibe Yulinda (Ma Chung Press, Universitas Ma Chung, 2025)
This study aims to evaluate the process of DNA and protein isolation from lemon leaf (Citrus limon L.), along with the analysis of their purity and concentration. The spectrophotometric analysis of DNA isolation results showed absorbance ratios (260/280 nm) of 2.6382 and 3.03372 for two samples, exceeding the standard range (1.7–1.9), indicating RNA contamination. Agarose gel electrophoresis results revealed no visible DNA bands, despite the use of specific primers for PCR. Protein isolation was conducted using the saltingout method with ammonium sulfate, and concentration analysis was performed using the Bradford method. The absorbance values of the samples ranged from 2.0375 to 2.0472, exceeding the optimal range (0.2–0.8), which affected the accuracy of the concentration calculations. The average protein concentration was 496.2989 ng/mcg. The high absorbance values were likely due to undiluted sample concentrations or contamination from phenolic compounds.